1985
DOI: 10.1080/03670244.1985.9990873
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and change of food consumption and nutrient intake among the Gidra in Lowland Papua

Abstract: Food consumption and nutrient intake of the Gidra in lowland Papua, who number 1,850 and inhabit 13 villages, were analyzed by compilation of five two-week (or twelve-day) records, in a single village in 1971 and in four different villages (including the above village) in 1981.The nutrient intake of the Gidra varied both over time and among the villages. Difference in food consumption patterns included different proportions of plant staples such as sago flour, garden crops and purchased cereals. The animal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 7 publications
0
45
0
Order By: Relevance
“…The 13 villages are sparsely arranged in an oval-shaped 4,000-square-kilometer territory, the southeastern end of which faces Daru, the capital of western Province, across a small strait. The Gidra have subsisted on exploitation of Metroxylon sago, slash-and-burn horticulture, hunting and fishing (OHTSUKA, 1983;OHTSUKA et al, 1985a). In the last several decades the Gidra have gradually been modernized, as indicated by the introduction of a cash economy, addition of such foreign foods as rice, flour and tinned fish to the diet, decrease of dependence on sago-making, and increase of out-migration to urban areas ( OHTSUKA et al, 1985a;OHTSUKA et al, 1985b).…”
Section: Methodsmentioning
confidence: 99%
“…The 13 villages are sparsely arranged in an oval-shaped 4,000-square-kilometer territory, the southeastern end of which faces Daru, the capital of western Province, across a small strait. The Gidra have subsisted on exploitation of Metroxylon sago, slash-and-burn horticulture, hunting and fishing (OHTSUKA, 1983;OHTSUKA et al, 1985a). In the last several decades the Gidra have gradually been modernized, as indicated by the introduction of a cash economy, addition of such foreign foods as rice, flour and tinned fish to the diet, decrease of dependence on sago-making, and increase of out-migration to urban areas ( OHTSUKA et al, 1985a;OHTSUKA et al, 1985b).…”
Section: Methodsmentioning
confidence: 99%
“…Some food composition tables for Western countries have been applied by researchers to pig meat despite the fact that Papua New Guinea pigs, even domestic ones, are markedly leaner (Buchbinder, 1973); perhaps Morren's (1977) report demonstrating that nearly half the total energy intake of the Miyanmin came from domestic and feral pigs was an example of misuse of the existing food composition tables. For sago starch, Ohtsuka et al (1985) pointed out that most food composition tables showed high energy content (up to 362 kcal per 100g) despite the fact that their own analyzed value was only 221 kcal; the difference was in the water content between the samples used for the published tables, which were obtained in the town markets long after production, and their own samples collected in the sago-eating villages. Calculation of per-person nutrient intake Conversion from raw nutrient intake data to the standardized intake per person (usually, per adult male) is necessary for comparison among different groups within the study subjects and with other populations or with standard values (or recom mendedallowances).…”
Section: Estimation Of Nutrient Intake From Food Consumptionmentioning
confidence: 99%
“…The common method of estimating the quantities of foods consumed out of the scope of the researcher is as follows. Each subject person is asked to recall any foods he/she has eaten outside the village, and the quantities of the foods are estimated by the subject and the researcher through comparison with several different-sized samples of the same kind of food (Harvey and Heywood, 1983;Ohtsuka et al, 1985). For this study, it is necessary to have made preliminary observations and preparations.…”
Section: Household-based Datamentioning
confidence: 99%
See 2 more Smart Citations